"La cotidianidad de las enfermeras asistenciales en la supervisión de las internas(os) de Enfermería en el Área Hospitalaria, Trujillo 2013" - Correa Mendoza, Jacqueline Maribel (2014)
The present study of qualitative boarding, fenomenológico aimed at analyzing comprehensiva her nursing cotidianidad of the helping nurses in the supervision of the interns in the hospitable area. The fact-finding scenario was Trujillo's Hospital Regional Docente place where labor the all-comers and the under consideration population was constituted for three helping nurses, the selection criteria were joining together which. The participating- subjects number was determined for the saturation method. The ethical criteria and customary scientist Were taken into account. information obtained through the deep interview three helping nurses that supervise the interns nursing itself. The discourses obtenidos were analizados emerging 4 empiric categories: You put under restraint considered as a health, supervision and evaluation personnel, I back up emotional, I work as a team.